Ramos-García, J. M. & Maier-Hirsh, E. (Coordinadores/as). (2024). Políticas de Estados Unidos y las Fronteras de México 2020-2022. Mexico: Colegio de la Frontera Norte. Págs. 232. - Pintor Sandoval, Renato (Internacionales. Revista en Ciencias Sociales del Pacífico Mexicano, 2025)
The book coordinated by José Maria Ramos García and Elizabeth Maier Hirsh (2024) entilid: "U.S. Policies and Mexico´´´´'s Borders 2020-2022", edited by Colef, is a work that is important to analyse for the discussion and helps un to understand the new probblems that indicated the establisgment of a higher phase of the U.S. State: the installation of a supranationalist government. Throught the fice chaptters, in addition to the introduction and conclusions, it address this issue and forces us to reflect on the current moment, which is emerging as a period market by the acceleration of conflicts, volatility, polarization and uncertaunty on global scale. Althrougt the document analyzes Joe Biden's administration, this comprendium invites us to consider the rise and returno of Trumpism in the United States. The crystallization of the rise of the extreme right-wing parties and the new aggresive agenda will cause societies to face socioeconomic barriers, the transgression of fundamental rights, the lack of compliance with multilateral agreements and the violation of guarantees that put democratic principlesnfirst in a country from an accumulated social and politics crisis.